Cover Image, Volume 39, Issue 11. Issue 11 (11th October 2018) - Zastrow, Diane B.; Baudet, Heather; Shen, Wei; Thomas, Amanda; Si, Yue; Weaver, Meredith A.; Lager, Angela M.; Liu, Jixia; Mangels, Rachel; Dwight, Selina S.; Wright, Matt W.; Dobrowolski, Steven F.; et al.
Abstract : On the Cover : This cover image is based on the Special Article Unique aspects of sequence variant interpretation for inborn errors of metabolism (IEM): The ClinGen IEM Working Group and the Phenylalanine Hydroxylase Gene by Diane B. Zastrow et al., Pages 1569–1580. DOI: 10.1002/humu.23649 .